Effects of Climate Change on the Potential of Water Harvesting from Air Humidity Under RCP4.5 and RCP8.5 Scenarios - Hadi Ramezani Etedali; Sakine Koohi; Zahra Partovi (Nīvār)
Extracting water from air humidity as one of the new and sustainable methods for providing water resources in areas with a lack of natural water resources and also in the conditions of drought is of great importance. Considering the influence of the amount of water that can be extracted from air humidity on changes in meteorological variables such as air temperature, wind speed and air humidity, therefore the potential of water extraction from air humidity can be strongly affected by climate changes. Therefore, the current research has been carried out with the aim of investigating the potential changes of water extraction from air humidity under RCP4.5 and RCP8.5 scenarios from the fifth climate change report. The results in the base period showed that the climate models have a suitable efficiency for investigating the potential of water extraction from air humidity, so that the average correlation index at the level of study stations is more than 0.67 and the value of the RMSE error index is 1.83 liters per square meter in The day is limited to In addition, the monitoring of water extraction conditions from air humidity under climate scenarios in the coming periods indicates the existence of an increasing trend at the 95% confidence level in the amount of water that can be extracted from air humidity, such as the value of Menkendall's non-parametric test under RCP4.5 and RCP8.5 scenarios. In the periods of 2026-2050 and 2076-2100, it is estimated to be more than 1.64. In general, based on the results, it was found that the northwest region of the study area has the greatest potential for the implementation of water extraction projects from air humidity. Therefore, due to the occurrence of global warming in recent years, the increase in water needs in different sectors and the consequent increase in pressure on the available water resources, the need to pay attention to this water source, planning and taking serious action for its use is felt more than ever. The results of the present research can be useful in planning for the sustainable management of water resources under the influence of global warming.